Study of the spread potato virus M in some areas of Nineveh Governorate - Ali Ali; Nabil Kassim; Juhayna Muhammad Ali (مجلة جامعة كركوك للعلوم الزراعية)
The results of serological diagnosis by using DAS-ELISA test on the potato plants showed the presence potato virus M (PVM), in terms of the yellow colour that appeared in the positive pits, and through the absorbance readings of the spectrometerrecorded the highest value in the Sherikhan samples, which reached 2.480, while its less value in Wana was 0.799 nm. the frequency of the virus in the Rabia was 42.1%, while the frequency of the virus in the Wana was 27.7%.Statgraphics 18 program was used with Kriging analysis to predict the probability of distribution of potato virus M and to determine the nature of its spread in the potato field in Al-Fadiliyah area by the visiting aphids (noncolonizing) and the resident aphids (colonizing). where it reached 58%, while the infection rate increased in the second and third trimesters by 45% and 43%, respectively.the spread of infections was random in the field, which indicates the role of aphids in as a vectors, whether it was the visiting aphids and the resident aphids. The spread of the virus has been associated with the insects that carry it in the field and the occurrence of secondary infections during the growing season, especially that the results of diagnosing aphids caught by The yellow sticky traps has two species of aphids, which are Myzus persica and Aphis fabae, the first species considered a visitor to the field first and other turns into a colonizid because it prefers to potatoes, while the other species is a visitor but non colonizid the field